2015
DOI: 10.1017/s1368980015001500
|View full text |Cite
|
Sign up to set email alerts
|

District wellness policies and school-level practices in Minnesota, USA

Abstract: Objective To compare the strength of district wellness policies with corresponding school-level practices reported by principals and teachers. Design District-level wellness policy data was collected from school district websites and, if not available online, by requests made to district administrators in the fall of 2013. The strength of district policies was scored using the Wellness School Assessment Tool. School-level data were drawn from the 2012 Minnesota School Health Profiles principal and teacher su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Discovering factors that are associated with high‐quality policies is crucial. Strong policies are related to greater correspondence between written language at the district level and school practices and the availability of calorie‐dense foods and beverages . Research suggests that schools with high‐quality written policies and adherence to implementation are characterized by supportive environments that champion SWPs, providing resources, oversight, and funding for wellness efforts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discovering factors that are associated with high‐quality policies is crucial. Strong policies are related to greater correspondence between written language at the district level and school practices and the availability of calorie‐dense foods and beverages . Research suggests that schools with high‐quality written policies and adherence to implementation are characterized by supportive environments that champion SWPs, providing resources, oversight, and funding for wellness efforts .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that more comprehensive policies are associated with student health, including lower prevalence of adolescent overweight and obesity and greater physical activity in students . Higher quality policies are also more likely to be implemented in schools and are related to healthier school practices such as lower availability of energy‐dense food and beverages . The association between high‐quality policies and increased implementation is likely due in part to precise policy language that provides enough detail for effective implementation at the school level.…”
mentioning
confidence: 99%
“…Each item was scored as a 0, 1, or 2: “0” indicates that there is no mention of the item in the policy; “1” indicates that the item is referenced with weak or vague language; and “2” indicates that there is a strong and specific policy addressing the item. This measure has established reliability for use in public health practice, and previous research has demonstrated that grantees can complete these assessments without bias . Grantees attended a training webinar and followed instructions posted on the WellSAT website.…”
Section: Methodsmentioning
confidence: 99%
“…The findings to date are mixed. Some studies have found significant relationships between written district wellness policies and practices that occur at the school level, and others have found that having a written policy does not increase the likelihood of the relevant school practice . One challenge faced in the current literature is that the written policy and implementation assessment tools are not always synchronized to match the policy with the practice.…”
mentioning
confidence: 99%
“…Research from other jurisdictions shows the important role school districts play in implementing food and beverages sales policies. In the United States, studies have found district policies influence students’ consumption of sugar-sweetened beverages and significantly reduce the availability of unhealthy items for sale (Larson et al 2016). Also in the US, researchers have proposed that weak district policies and lack of accompanying resources for enforcement from the district level potentially perpetuate poor school food and beverage environments (Bergman et al 2015).…”
Section: Introductionmentioning
confidence: 99%